Procedural Pain: Systematic Review of Parent Experiences and Information Needs. (June 2018) - Gates, Allison; Shave, Kassi; Featherstone, Robin; Buckreus, Kelli; Ali, Samina; Scott, Shannon D.; Hartling, Lisa
Parents wish to reduce their child's pain during medical procedures but may not know how to do so. We systematically reviewed the literature on parents' experiences and information needs related to managing their child's pain for common medical procedures. Of 2678 records retrieved through database searching, 5 were included. Three additional records were identified by scanning reference lists. Five studies were qualitative, and 3 were quantitative. Most took place in North America or Europe (n = 7) and described neonatal intensive care unit experiences (n = 5). Procedures included needle-related medical procedures (eg, venipuncture, phlebotomy, intravenous insertion), sutures, and wound repair and treatment, among others. Generally, parents desired being present during procedures, wanted to remain stoic for their child, and thought that information would be empowering and relieve stress but felt unsupported in taking an active role. Supporting and educating parents may empower them to lessen pain for their children while undergoing medical procedures.